Peran Masjid dalam Pendidikan Akhlak - Ismail, Ismail; Prahastiwi, Eka Danik; Wahyuningsih, Diah (ARZUSIN, 2022)
The mosque is the oldest Islamic educational institution that has existed since the time of the Prophet Muhammad. Its existence needs to be maintained and maintained until now. Judging from its history, Muslims have used mosques for places of worship, educational institutions and Islamic knowledge. Moral education cannot be separated from the scope of Islamic education. Because, moral education aims to achieve perfect morals is the culmination of the purpose of implementing Islamic education itself. In other words, a Muslim cannot be said to be perfect in his religion if the morals in his life do not reflect good morals. This study aims to determine the role of mosques in moral education for the Tegalombo community. The research method used is descriptive qualitative with a content analysis approach of library research plus field research with observation, interviews and documentation research instruments. The results obtained from the study that the Baitus Somad mosque located in Tegalombo plays a very important role in moral formation for the Tegalombo community in particular and visitors in general because the role of honest coffee is used as a medium to habituate the community to be honest and learn anti-corruption, secondly, the role of Gazibu is able to diverting the negative behavior of teenagers, the three Sunday night huts can provide religious knowledge for teenagers.